Epoxy Resins: From Chemistry to Clinic - O'Boyle, Niamh (My University, 2019)
Epoxy resin systems (ERS) are commercial thermosetting products used in many diverse applications due to their outstanding performance and resistance. The global epoxy resins market accounted for $7.9 billion in 2016 and is expected to reach $11.5 billion by 2022. Their usage is increasing despite widespread contact allergy to ERS. Epoxy chemicals are implicated in both occupational and non-occupational allergic contact dermatitis (ACD), with higher prevalence (11.7 – 12.5%) in occupational settings. Workplace studies found exceptionally high rates of ACD from ERS in aircraft manufacturing workers, marble workers, painters, metalworkers and construction workers. Educational and protective measures are not always effective. We have taken an alternative, complimentary approach to reduce ACD to epoxy resins by modifying their chemical structures to control reactivity. It is a challenging task to reduce the adverse skin sensitizing effects of ERS while maintaining their excellent ability to form thermosetting polymers, as both of these properties are dependent on the inherent reactivity of the terminal epoxy groups. Focusing on the epoxy resin monomers DGEBA and DGEBF, we have designed compounds containing terminal epoxy groups with reduced reactivity by alteration of the total chemical structure. We have designed technically effective, less reactive epoxy resin monomers. Our alternative monomers were less sensitizing than DGEBA and DGEBF in vivo, as assessed by the LLNA, and showed little or no cross reactivity with DGEBA in a clinical study. We will present results from chemical design to in vitro and in vivo reactivity studies and clinical assessment.
Occupational and Environmental Exposure of the Skin to Chemicals
Keywords: Research Subject Categories::PHARMACY; Allergic Contact Dermatitis; Epoxy Resins; Skin Allergy; Bisphenol A; Bisphenol F; DGEBA; Immunology, Inflammation & Infection; ALLERGIC CONTACT DERMATITIS; BISPHENOL-A; EPOXY; EPOXY RESINS; Skin Allergy